Palliative Care for Hospitalized Patients With Stroke: Results From the 2010 to 2012 National Inpatient Sample - Singh, Tarvinder (Stroke, 2017)
BACKGROUND AND PURPOSE—: Substantial variability exists in the use of life-prolonging treatments for patients with stroke, especially near the end of life. This study explores patterns of palliative care utilization and death in hospitalized patients with stroke across the United States. METHODS—: Using the 2010 to 2012 nationwide inpatient sample databases, we included all patients discharged with stroke identified by International Classification of Diseases-Ninth Revision codes. Strokes were subclassified as ischemic, intracerebral, and subarachnoid hemorrhage. We compared demographics, comorbidities, procedures, and outcomes between patients with and without a palliative care encounter (PCE) as defined by the International Classification of Diseases-Ninth Revision code V66.7. Pearson χ(2) test was used for categorical variables. Multivariate logistic regression was used to account for hospital, regional, payer, and medical severity factors to predict PCE use and death. RESULTS—: Among 395 411 patients with stroke, PCE was used in 6.2% with an increasing trend over time (P<0.05). We found a wide range in PCE use with higher rates in patients with older age, hemorrhagic stroke types, women, and white race (all P<0.001). Smaller and for-profit hospitals saw lower rates. Overall, 9.2% of hospitalized patients with stroke died, and PCE was significantly associated with death. Length of stay in decedents was shorter for patients who received PCE. CONCLUSIONS—: Palliative care use is increasing nationally for patients with stroke, especially in larger hospitals. Persistent disparities in PCE use and mortality exist in regards to age, sex, race, region, and hospital characteristics. Given the variations in PCE use, especially at the end of life, the use of mortality rates as a hospital quality measure is questioned.